Disability Identity: Perspective for Policy Formulation - Widadsyah, Muhammad Azhar (The Center for Disability Studies and Services Brawijaya University, 2023)
Policies regarding people with disabilities (PWDs) are formulated without PWDs perceptive and often rule out disability identity owned by PWDs. Those policies potentially result in further issues regarding PWDs empowerment. This research aims to investigate about factors that shape disability identity and how disability identity could provide a new perspective in policy formulation. Researchers interviewed seven PWDs with different disability conditions to gain their perspective on their perception of disability identity. Furthermore, data were analyzed to form three factors of disability identity, which are structural factors, personal and social interaction factors, also organizational development factors. This research also explains how disability identity could be implemented in public policy formulation through some aspects that could be considered further in policy regarding of disability and PWDs.